2020
DOI: 10.1098/rspa.2020.0124
|View full text |Cite
|
Sign up to set email alerts
|

Knot polynomials of open and closed curves

Abstract: In this manuscript, we introduce a method to measure entanglement of curves in 3-space that extends the notion of knot and link polynomials to open curves. We define the bracket polynomial of curves in 3-space and show that it has real coefficients and is a continuous function of the curve coordinates. This is used to define the Jones polynomial in a way that it is applicable to both open and closed curves in 3-space. For open curves, the Jones polynomial has real coefficients and it is a continuous function o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 42 publications
(75 reference statements)
2
50
0
Order By: Relevance
“…where K i is a knotoid that appears in a projection of l and p(K i ) is the geometric probability that the projection of l gives the knotoid K i and K(l) is the set of possible knotoids that can result as a projection of l. In [51], it was shown that p(K i ) is a continuous function of the curve coordinates. Thus, w k (l n ) is a continuous function of the coordinates of l n .…”
Section: Proposition 37 Let L Denote An Open Curve In 3-space Then the Kth Vassiliev Measure Of L W K (L) Is A Continuous Function Of Thementioning
confidence: 99%
See 4 more Smart Citations
“…where K i is a knotoid that appears in a projection of l and p(K i ) is the geometric probability that the projection of l gives the knotoid K i and K(l) is the set of possible knotoids that can result as a projection of l. In [51], it was shown that p(K i ) is a continuous function of the curve coordinates. Thus, w k (l n ) is a continuous function of the coordinates of l n .…”
Section: Proposition 37 Let L Denote An Open Curve In 3-space Then the Kth Vassiliev Measure Of L W K (L) Is A Continuous Function Of Thementioning
confidence: 99%
“…We can express p j 1 ,j 2 ,j 3 ,j 4 as the joint probability that e j 1 , e j 3 and e j 2 , e j 4 both cross. In [51], it was proved that the geometric probability that e j 1 , e j 3 cross, p j 1 ,j 3 , and the geometric probability that e j 2 , e j 4 cross, p j 2 ,j 4 , are continuous and are equal to the areas of the corresponding quadrangles on the sphere. Their intersection, p j 1 ,j 2 ,j 3 ,j 4 , is the area of the intersection of the two spherical quadrangles.…”
Section: The Double Alternating Self-linking Integral Of Curves In 3-spacementioning
confidence: 99%
See 3 more Smart Citations